Choosing which ear to implant in adult candidates with functional residual hearing - Fielden, Claire A.; Mehta, Rajnikant L.; Kitterick, Pádraig T. (Taylor & Francis, 2016)
This study examined whether audiologists consider the potential benefits of contralateral hearing aid use following cochlear implantation when recommending which ear to implant in UK adult candidates with residual hearing. Thirty-four audiologists from providers of adult implantation services completed a decision-choice experiment. Clinicians were willing to consider recommending that the poorer ear be implanted, provided it had been aided continuously, suggesting that their decision making seeks to preserve access to residual hearing in the non-implanted ear where possible. Future approaches to determining candidacy should therefore consider that a sub-set of patients may obtain additional benefit from this residual hearing following implantation.